Prediction of Pekanbaru City rainfall using dynamic models - Yunita, Esy; Retnawaty, Sri Fitria; Fitrya, Neneng (Indonesian Physics Communication, 2024)
The need for predictions is very necessary in various sectors of life, one of which is rainfall predictions. The threshold value for PM10 particles that is allowed to be in ambient air is, 150 µgram/m3/day). The aim of this research is to create a dynamic model predicting Pekanbaru City's rainfall for the next 3 years. Rainfall prediction in this research was carried out using the dynamic system modeling method with Powersim software. The data used is BMKG data for the Pekanbaru City for 5 years (2015 – 2019) using 4 parameters, namely rainfall, air humidity, wind speed and temperature. Prediction results show that air humidity in Pekanbaru City has the same pattern as BMKG, namely the highest month is December and the lowest is August. Wind speed prediction results are highest in July and lowest in May. The highest temperature in Pekanbaru City is in April and the lowest is in January. Rainfall for 2020 – 2021 is predicted to experience light rain on average, because it has the same data pattern on the variables that influence it. So it can be interpreted that the validation results for air humidity, wind speed and temperature in Pekanbaru City show that they are valid because they do not exceed the limit value of ≤ 5%.